Nghiên cứu đánh giá khả năng thoát lũ sông Thái Bình đoạn Cát Khê-Ngọc Điểm - Đoàn, Thanh Hằng (2011)
Tác giả: Đoàn Thanh Hằng, KS; Đoàn Chí Dũng; Trần Thị Bích Nga; Đào Thị Quy; Phạm Văn Sơn -- Từ khóa: Lũ; Thoát lũ; Sông Thái Bình